Detection of volatile organic compounds (VOCs), aliphatic amines, using highly fluorescent organic-inorganic hybrid perovskite nanoparticles. (December 2017) - Kim, Sung-Hoon; Kirakosyan, Artavazd; Choi, Jihoon; Kim, Jong H.
Abstract: In this work, a fluorescence chemosensor based on organic-inorganic hybrid CH3 NH3 PbBr3 perovskite nanoparticles has been investigated for the detection of volatile organic compounds (VOCs), aliphatic amines (monoethylamine, diethylamine, and trimethylamine). Perovskite films showed fast (<1 s), highly discernible (89%), and reversible/irreversible fluorescence quenching behavior in response to the amine vapor exposure. Detection mechanism was confirmed by crystalline structural analysis based on X-ray diffraction (XRD) measurements and quantum chemical calculations, which proved that fluorescence quenching originates from the structural conversion from perovskite to its components by reversible or irreversible hydrogen bonding interaction between perovskite and aliphatic amines. This study suggests a simple but very effective strategy for naked eye-based fluorescence sensing of the colorless and harmful aliphatic amine vapors. Highlights: ● Organometal halide perovskite nanoparticles are used as aliphatic amines vapor chemosensor. ● Fast (<1sec) and reversible/irreversible detection of aliphatic amines gas is demonstrated based on fluorescence quenching. ● Interaction of perovskite with polar aliphatic amines influencing fluorescence quenching are investigated.